IMPLEMENTASI PROGRAM INDONESIA PINTAR PADA SMPN 3 BANJARBARU KECAMATAN CEMPAKA KOTA BANJARBARU - Tamliha Harun (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2021)
The purpose of this research is to find out how the implementation of the Smart Indonesia Program (PIP) at SMPN 3 Banjarbaru, Cempaka Subdistrict, Banjarbaru City, is it in accordance with the Regulation of the Director General of Education of the Ministry of Education and Culture Number: 1881 / D / BP / 2019 concerning Guidelines for Implementing the Smart Indonesia Program at the Basic Education level. This research is a descriptive study, with data collection techniques interview, observation, and documentation, then the results are analyzed qualitatively. The results of this study indicate that: a. Implementation of the Smart Indonesia Program (PIH), through the Smart Indonesia Card (KIP) at SMPN 3 Banjarbaru has been running well and effectively, in accordance with applicable regulations; b. The number of students receiving assistance from the Smart Indonesia Program through the Smart Indonesia Card at SMPN 3 Banjarbaru was 228 students. However, there are some people who actually no longer meet the requirements, because the income of the parents / guardians of the students concerned has increased from before. KIP recipient students, the process of recapitulation, verification and input of student KIP recipient student data to Dapodik, until the disbursement and use of KIP funds by recipient students; d. The Smart Indonesia Program (PIH), through the Smart Indonesia Card (KIP) at SMPN 3 Banjarbaru, is very beneficial for students from poor or underprivileged families, so that the number of students dropping out of school can be reduced; e. However, there were still some students who received KIP or their guardians who did not understand the use of KIP funds, so they were used to finance expenses outside the context of their educational / school needs.